Cancer and the World's Poor: What's a Gynecologic Cancer Specialist to Do?. Issue 10 (October 2016) - Randall, Thomas C.; Goodman, Anne Kathryn; Schmeler, Kathleen; Durfee, John; Pareja, Rene; Munkarah, Adnan; Rulisa, Stephen; Ghebre, Rahel; Trimble, Edward L.; Chuang, Linus
Abstract : (Abstracted from Gynecol Oncol 2016;142:6–8) Remarkable improvements have been made over the past 5 decades in care of women with gynecologic malignancies. In the developed world, most women with uterine cancer are cured, and both survival and quality of life of women with ovarian cancer have improved.